2012
DOI: 10.2147/lra.s35535
|View full text |Cite
|
Sign up to set email alerts
|

Continuous spinal anesthesia for lower limb surgery: a retrospective analysis of 1212 cases

Abstract: BackgroundContinuous spinal anesthesia is a very reliable and versatile technique for providing effective anesthesia and analgesia. However, the incidence of possible complications, including postdural puncture headache or neurological impairment, remains controversial. Therefore, the aim of the present retrospective study was to analyze a large number of patients for the incidence of adverse events after continuous spinal anesthesia with a microcatheter.MethodsThis retrospective study was conducted on 1212 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 18 publications
4
25
0
Order By: Relevance
“…This result was in accordance with Lux [5] who concluded that continuous spinal anesthesia appears to be a safe and appropriate anesthetic technique in lower leg surgery for aged patients. Also was in accordance with Imbelloni et al [8] whose found that, CSA provided good surgical conditions with low incidence of complications.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result was in accordance with Lux [5] who concluded that continuous spinal anesthesia appears to be a safe and appropriate anesthetic technique in lower leg surgery for aged patients. Also was in accordance with Imbelloni et al [8] whose found that, CSA provided good surgical conditions with low incidence of complications.…”
Section: Discussionsupporting
confidence: 91%
“…In 1907, Continuous spinal anesthesia (CSA) was first described for anesthesia practice and nowadays the technique is used in Europe for more cardiovascular stability in high-risk patients undergoing lower limb and lower abdominal surgery [5] . CSA allows titration of small doses of local anesthetic, achieves the appropriate level and duration of anesthesia with minimal hemodynamic changes.…”
Section: Introductionmentioning
confidence: 99%
“…CSA allows the administration of local anaesthetics in smaller doses titrated to the patient's requirements, has minimal cardiovascular and respiratory side effects and provides postoperative analgesia, allowing the application of intrathecal local anaesthetics postoperatively [6]. Kilinç et al [7] compared the haemodynamic consequences and the effectiveness of CSA with unilateral spinal anaesthesia in elderly patients undergoing hip surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension was reported as more common during spinal anesthesia in a supine position compared to the lateral decubitus position in elderly patients with low ejection fraction [9]. Moreover, Lux et al [6] analysed 1212 cases that underwent surgery of the lower extremities with continuous spinal anaesthesia using a 28-gauge microcatheter. No major complications were reported in any of these patients, and it was concluded that CSA using a 28-gauge microcatheter appears to be a safe and appropriate anaesthetic technique in lower leg surgery for aged patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in a study (9) investigating the effect of spinal block on patients with low cardiac output who underwent lower limb surgery, hypotension and the need for vasopressor support due to spinal anaesthesia were not observed in any of the Turk J Anaesth Reanim 2015; 43: 55-7 patients. Moreover, Lux et al (5) analysed 1212 cases who underwent surgery of the lower extremities with continuous spinal anaesthesia using a 28-gauge microcatheter. They reported no major complications in any of these patients, and they concluded that continuous spinal anaesthesia using a 28-gauge microcatheter appears to be a safe and appropriate anaesthetic technique in lower leg surgery for aged patients.…”
Section: Discussionmentioning
confidence: 99%